Equilibrium or imbalance? Regional variations and evolutionary traits of two-way FDI coordination level in Yangtze River economic belt - Pan, Xiaochun; Xiao, Yi; Liu, Zhengjun (Frontiers in Environmental Science, 2022)
Based on the VAR model, the two-way FDI data of the Yangtze River Economic Zone from 2005 to 2019 were used as the specimen. The correlation of the two-way FDI was observed using the VAR impulse effect through ADF root test and lag structure laboratory testing. The original study results demonstrated that there have been disparities in the spatial and temporal evolution of FDI and OFDI coordination levels between the eastern, central, and western city groups in the Yangtze River Economic Belt region from 2005 to 2019.The unequal expansion of FDI and OFDI is the phenomena that results in the gap between eastern and western cities. The development of the coupling coordination level between the east and west areas has been unequal due to variances in the natural environment, trade value, corporate expansion, and other variables.Contrarily, the Yangtze River Economic Belt's western urban agglomerations have a lower level of coupling and coordination development than the region's eastern urban agglomerations, with an overall declining phenomena from east to west. The coupling and coordinated development of two-way FDI within the economic belt, which has a significant impact on the rationalization of regional resource allocation, industrial structure optimization, and technology iteration with civilization construction, can be greatly facilitated, in our opinion, by strengthening uncoordinated regional development infrastructure and deepening regional economic-industrial links.